Estimación de Carbono Orgánico del suelo destinado a la generación de forrajes en la Quinta Experimental El Padmi, provincia Zamora Chinchipe - Zumba Valarezo, Silvana Maribel (2024)
The Ecuadorian Amazon has experienced an alarming increase in deforestation and permanent conversion to pastures and crops. This trend has generated a significant increase in greenhouse gas emissions, causing profound changes to the region's ecosystems. Moreover, it has adversely affected the soil's physical, chemical, and biochemical properties, as well as its natural fertility and productivity. As a consequence of these processes, the degradation and loss of its quality has accelerated (Tiria et al., 2018). In the framework of this experimental research, the impact of Tithonia diversifolia and Thichanthera gigantea forage species, in combination with two types of fertilizers, pollinasse and nutrisane, on the physicochemical properties and organic carbon storage of the soil of Quinta Experimental El Padmi was evaluated. In the study, three areas were studied, one of which was treated as a control, with both types of forages, but without manure. Two samples were taken before and after the application of fertilizers, focusing on the first 20 cm of soil depth. Disturbed samples were used to analyze soil pH, electrical conductivity (EC), cation exchange capacity (CEC), organic matter (OM) and texture, while undisturbed samples were used to determine bulk density (DB). The results revealed a higher organic carbon (OC) storage content in the control area (77.62 tCha-1) compared to the other areas. In T. gigantea with pollinaza 69.05 tCha-1 and with nutrisane 56.33 tCha-1 were recorded, while in T. diversifolia with pollinaza 61.43 tCha-1 and with nutrisane 46.43 tCha-1 were obtained. These results indicate a more effective association between forage species, although there was an increase in CO in T. diversifolia in areas where fertilizers were applied. In conclusion, it can be concluded that cation exchange capacity (CEC) had a greater impact on CO content than bulk density (DA), organic matter (OM), pH, or cation exchange capacity (EC).